ANALISIS KEKUATAN SAMBUNGAN LAS SMAW ( SHIELDED METAL ARC WELDING ) PADA MARINE PLATE ST 42 AKIBAT FAKTOR CACAT POROSITAS DAN INCOMPLETE PENETRATION - Mulyatno, Imam Pujo; Jokosisworo, Sarjito (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2008)
At this moment, weld engineering is applied widely in tacking on joints at construction of steel building, especially at ship building. All important in weld engineering is when process tacking on weld metal with steel metal to be one unities. It mean, the strength of metal result by welded must equal to the original metal. Generally, that thing is inaccessible cause by weld defect formed. Result of survey in JMI indicates that often happened problem at weld joint part of construction of hull causing existence of fraction or crack at the division. Because, hull is main part which received many forces, in water compressive force ( hydrostatic ) and ship attractive force on top of wave ( sagging ) and or in trough of wave ( hogging ). Even, at the moment of ship in full cargo condition or when at dock, ship must can maintain the selfish strength. In the research, will be checked weld defect influence incomplete penetration and porosity formed at SMAW method, evaluated from tensile and compressive strength as the application of force received by ship.from the result, indicates that tensile strength is optimum happened at the normal joint plate without heat treatment about 464, 50 Mpa, while tensile strength is lowest at joint plate condition of heat treatment 6000 C about 351,23 Mpa. for optimal of compressive strength happened at normal joint of plate without heat treatment about 872, 17 N/mm2, while compressive strength is lowest at joint plate condition of heat treatment 3000 C about 684 N/mm2. In this experiment, weld defect of incomplete penetration and porosity is not too effect a weld joint strength caused all to fracture happen in base metal is not it in weld joint or weld metal, however for all weld defect must be minimizes